TOLERANSI BERAGAMA SISWA SEKOLAH LANJUTAN TINGKAT ATAS (SLTA) - Qowaid Qowaid (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2012)
Interreligious tolerance is a basic element needed for developing attitude in understanding and respecting diffrences among plural communities in Indonesia. That kind of attitude not only from religion side, but also from culture, ethnics and language sides. Students of high school has importance position and big potention in creating interreligious tolerance. The problem is, to what degree of tolerance among high school students exist on this case. This research is done quantitatively with all students in the provinces of Java and Sulawesi in survey based for collecting data. The results of research shows that in general attitude of the students toward religious life is quite moderate and tolerance. There is tendency in not tolerant for a small number of students. It is needed to spur all students in accelerating of attitude toward tolerance.